Evaluation of Dynamic Foraminal Stenosis with Positional MRI in Patients with C6 Radiculopathy-Mimicking Pain: A Prospective Radiologic Cohort Study - Kaya, Ozcan; Sariyilmaz, Kerim; Tutpinar, Yildiray; Cakmak, Mehmet Fevzi; Cakir, Mehmet Semih; Ozkunt, Okan (HINDAWI LTD, 2022)
Objective. Patients with a C6 radiculopathy-mimicking complaint are always in the gray zone if the diagnosis is not clear. The aim of the study is to make the diagnosis clear if the neck and shoulder pain is caused by a dynamic stenosis of the neural foramen at the C5-C6 level. Methods. Patients with a C6 radiculopathy-mimicking complaint were included in the study. Patients had a cervical spine magnetic resonance imaging (MRI) at the normal limits, or a minimal protrusion at the C5-C6 level underwent a dynamic MRI procedure. We measured the foraminal area and spinal cord diameter (SCD) at the C5-C6 level by using the PACS system ROI irregular are determination integral embedded to PACS. Inter- and intraobserver reliability of measurements was evaluated. Results were analyzed statistically, and a p value < 0.05 was accepted as statistically meaningful. Results. A total of 23 patients between January 2019 and June 2019 were included in the study. There were 10 men and 13 women, and the mean age was 41.3 (range 33-53). Foraminal area decrease at C5-C6 in extension and increase in flexion when compared with the neutral position was statistically significant (p < 0.001). Foraminal area changes between the complaint side and the opposite side was not statistically different (p > 0.05). Interobserver and intraobserver reliability of measurements were classified as in almost perfect agreement. Conclusions. Our present work presented dynamic and positional foraminal changes in MRI with radiculopathy-mimicking patients. Soever, we did not find a difference between the clinical complaint side and the opposite side in radiculopathy-mimicking patients. Cervical radiculopathy pain should not be attributed only to foraminal sizes. PACS embedded irregular area measurement integral allows the easy measure of a big number of patients without additional set-up and digital work requirements.